My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppression; thématiques; travail; violences; états-unis

Travail invisible : portraits d'une lutte féministe inachevée - Robert, Camille; Toupin, Louise (Remue-ménage, 2018)
Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes
Keywords: amériques; approches et analyses; canada; care; fem1300; femmes* autochtones; femmes* immigrantes; inégalités; premier cycle; québec; racisme; régions géographiques; sexisme; systèmes d'oppression; thématiques; travail; travail domestique; travail du care; travail du sexe

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppression; thématiques; travail